PHOTOCHEMOPROTECTION OF CAULERA SPP ACTIVE COMPONENT ON RAT MODEL SKIN - Wiraguna, A. A. G. P.; Pangkahila, W.; Mantik-Astawa, and N. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol 7 No 2 (2013): IJBS Vol2 No2, 2013)
Caulerpa spp. including seaweed and macro-algae can be found in a large number at Coastal Serangan, Bali-Indonesia. Caulerpa spp was historically used for food and vegetable. However, in our today life, this plant was applied as material for skin care products, especially for UV protection. The aim of this study is to know the active component of caulerpa spp extract and its inhibition of premature skin aging induced by UV-B radiation through collagen expression. This was descriptive and experimental research applying a randomized posttest only control group design. Active component contained in the caulerpa spp extract are carotenoid, vitamin A, C, and E, polyphenols, minerals and amino acids. Topical application of caulerpa spp can suppress the UV-B radiation induced collagen damage. Increased of collagen expression in all groups of caulerpa spp. just as good as astaxanthin group in improving collagen expression and 0.2% of caulerpa spp. extract is the most effective dose in improving collagen expression.
Keywords: Caulerpa spp, UV-B rays, collagen, expression